Newborn Screening for Biotinidase Deficiency. The Experience of a Regional Center in Italy - Maguolo, Alice; Rodella, Giulia; Dianin, Alice; Monge, Irene; Messina, Martina; Rigotti, Erika; Pellegrini, Francesca; Molinaro, Grazia; Lupi, Fiorenzo; Pasini, Andrea; Campostrini, Natascia; Ion Popa, Florina; et al. (Frontiers in Pediatrics, 2021)
Introduction: Biotinidase deficiency (BD) is an autosomal recessive disease causing a defect in the biotin releasing enzyme. Newborn screening (NBS) allows early diagnosis and treatment, ensuring excellent prognosis. The aim of this study was to describe our experience in the diagnosis, treatment and follow up showing key strategies and unsolved questions of the management of BD patients. Methods: We analysed data of patients identified by the Regional Centre for Newborn Screening of Verona and followed by the Inherited Metabolic Disease Unit of Verona, and Neonatal Intensive Care Unit of Bolzano, Italy, from 2014 to 2020. Results: 37 patients were diagnosed by NBS (5 profound and 32 partial BD), with a total incidence of 1:5996. All were started on biotin at diagnosis and presented no symptoms at follow up. Analysis of parents and siblings led to identification of 5 asymptomatic patients with partial BD: 1 asymptomatic parent and 4 young siblings. Genetic analysis of BTD gene identified 17 different genotypes and 1 mutation not previously known. Discussion: Our data confirm that NBS introduction had a dramatic impact on BD diagnosis and the incidence has increased significantly compared to other areas. Partial defects are more common than profound and have a distinctive genotype. Partial BD treatment is still controversial even at what dose of biotin and for how long. At the end BD treatment is very easy and inexpensive and prevents severe neurological damage. Sharing experiences is essential to achieve guidelines for treatment and follow-up and a better genotype-phenotype correlation.